THE NECESSITY OF LEGAL LITERACY IN THE CONTEXT OF ARTIFICIAL INTELLIGENCE IN THE DIGITAL WORLD - Yoqubjonov Ma’rufjon Odiljon o’g’li (Western European Studies, 2025)
This article analyzes the role and necessity of legal literacy in the modern digital environment, where artificial intelligence technologies are being widely implemented. The authors examine pressing issues such as AI-based algorithmic governance, data privacy, individual rights, and legal accountability, drawing upon international legal standards, academic research, and global practices. The article also offers conclusions and practical recommendations for improving legal literacy
Keywords: legal literacy; artificial intelligence; algorithmic governance